COMPERATION CHARACTERISTICS OF CONNECTIVE TISSUE TURNOVER AND FUNCTIONAL CHARACTERISTICS OF LEFT VENTRICLE IN PATIENTS WITH ARTERIAL HYPERTENSION AND ISCHEAMIC HEART DISEASE - Ванджура, Я. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Comparative data regarding functional state of connective tissue matrix and hemodynamic values of myocardium in patients with arterial hypertension without concomitant ischemic heart disease and those after myocardial infarction are highlighted in the article. It was revealed that combination of arterial hypertension and myocardial infarction debilitates endothelial dysfunction, destructive-synthesizing processes disorders of connective tissue and worsens main functional and structural characteristics of heart.